Pembelajaran pendidikan seni visual di kalangan pelajar orang asli (IR) - Siti Hayati Mohd Yusoff (2009)
When we discuss about influence in the learning process among Orang Asli students, who comes from different ethnic among themselves, in schools, we cannot ignore about the issue of development and their way of thinking based on this unique background among Orang Asli community, I felt a calling to do a research about social influence which focuses on factors that influences the process of acquiring attitude among Orang Asli students, when leraning Visual Art as a subject. Based on my observation in these 9 years, I found that in the livelihood of the Orang Asli community, Art has a high value in their community. They like entertainment, crafts, nature and 'laid back' situations which doesn't require mind improvement. Orang Asli students like doing physical works but not works which require mind application. This is due to social influence in their life. Therefore, before doing this research, a few aspects have to be identified like understanding the background of Orang Asli social-culture and practice, as well attitude and characters of the Orang Asli community which is different from other races. All these aspects will then be looked into to understand the issues of belief in their community. Some art works produced by their ancestors and parents, encourages the capability among Orang Asli students to observe their surrounding. They do have knowledge based on what they see and experience with their family, thus the painting produced by Upper 6 Orang Asli students is influenced by their "belief among the community, which has be passed on from generations to generations.